Brand experience and brand loyalty: The moderating role of brand trust and the mediating role of brand love in Pakistani smartphone users - Imran Sarmad; Muhammad Ahsin Imtiaz; Syed Muhammad Hassan Bukhari; Ali Abbas; Ismat Munir (Pakistan Journal of Commerce and Social Sciences (PJCSS), 2024)
The current study looks at the relationships in the Pakistani smartphone market between brand experience, brand love, and brand loyalty. In addition, we also study brand trust's moderating effect. The data was collected from 300 Pakistani smartphone users. Structural equation modelling (SEM) and PROCESS macro model 8 were used for data analysis. This research showed that the experience of a brand is a significant factor in determining both love and loyalty to that brand. The outcomes of the research indicated that there was a substantial relation between brand experiences and brand loyalty, with brand love serving as a mediating component in this relationship. We found that there was a statistically significant relationship between brand trust and brand experiences as well as brand loyalty. On the other hand, the association between brand experiences and brand love was tempered by confidence in the brand concerned. This pioneering study examines Pakistani smartphone users' interests and behaviors and it also examines how brand trust mediates these variables.
Keywords: 330; Brand experience; brand love; brand trust; brand loyalty; smartphone users; Pakistan